Colonial India in the ILO and International Law - V Shenoy, Amritha (Christ University Law Journal, 2022)
With an ideological domination of Western academic discourses with respect to international law, there is a lack of a holistic approach to international law with a distinct disadvantage to third world nations and their citizens. History of international law has most often been documented from a European perspective. This paper attempts to fill this gap by narrating an alternative history of international law and thus seeks to move beyond this Euro-centric ‘turn to history’ with a TWAIL perspective. The paper traces India’s relationship with international law. Firstly, the paper examines this anomalous position of colonial India and its princely states at the international organisations. It recognises that although Indian membership at the ILO was merely representative with a deep and entrenched British control, Indian representatives at the ILO attempted to further true Indian multicivilizational interests at their meetings. In the above context, the paper traces the Indian struggle to be represented at international fora, including the ILO. Finally, the paper concludes by questioning the legitimacy of international law in the colonial period. Therefore, the paper attempts to reflect on this history of international law, with a diverse and inclusive perspective.